The implication of fertility rate and life expectancy growth towards ASEAN economic growth - Yeo Soon Jian; Janice L. H. Nga (Fakulti Kemanusiaan Seni dan Warisan, UMS, 2019)
This paper investigates the implication of demographic change towards economic growth in ASEAN from 1990 to 2018 by using the panel data from the World Bank Indicators (2019). Since 2010, ASEAN had experienced a continuous decline in GDP per capita growth. A number of literature review report demographic change was the factor that influence GDP per capita growth. Both Panel Least Squares (PLS) and Random Effect (RE) estimation reported that increasing in the labour participation and productivity had a positively influence on economic growth due to economic of scale and competitiveness improvement. Moreover, both fertility rate and life expectancy growth had negatively influence on economic growth where increase in fertility rate and life expectancy raise the child and aged dependency. However, the empirical result show that share of working-age population had no implication towards the economic growth due to the government intervention on interest rate and social security expenditure. Changing in fertility rate and life expectancy provide an important economic opportunity for ASEAN countries expectedly in child dependency reduction and increasing in household saving for both human and physical capital investment. However, the effective policies that may affect labour participation and productivity additional family planning programs should be considered.